Propagation characteristics of stress waves induced by underground blasting under the influence of rock-soil interfaces - Meng, Xianzhong; Zhou, Chuanbo; Jiang, Nan; Zhang, Zhen; Yang, Yumin; Wu, Di (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
The Rock-soil interface is a common geological interface. Due to mechanical differences between soil and rock, the stress waves generated by underground blasting undergo intense polarization when crossing the rock-soil interface, making propagation laws difficult to predict. Currently, the characteristics of the impact of the rock-soil interface on blasting stress waves remain unclear. Therefore, the vibration field caused by cylindrical charge blasting in elastic rock and partial-saturation poro-viscoelastic soil was solved. A forward algorithm for the underground blasting vibration field in rock-soil sites was proposed, considering medium damping and geometric diffusion effects of stress waves. Further investigation into the influence of rock and soil parameters and blasting source parameters revealed the following conclusions: stress waves in soil exhibit dispersion, causing peak particle velocity (PPV) to display a discrete distribution. Soil parameters affect PPV attenuation only within the soil, while blasting source parameters affect PPV attenuation throughout the entire site. Multi-wave coupling effects induced by the rock-soil interface result in zones of enhanced and attenuated PPV within the site. The size of the enhancement zone is inversely correlated with the distance from the blasting source and positively correlated with the blasting source attenuation rate and burial depth, providing guidance for selecting explosives and blasting positions. Additionally, PPV attenuation rate increases with distance from the rock-soil interface, but an amplification effect occurs near the interface, most noticeable at 0.1 m. Thus, a sufficient safety distance from the rock-soil interface is necessary during underground blasting.